Draft Genome Sequence of the Putrescine-Producing Strain Lactococcus lactis subsp. lactis 1AA59 - Ladero, Victor (Genome Announc, 2015)
We report here the 2,576,542-bp genome annotated draft assembly sequence of Lactococcus lactis subsp. lactis 1AA59. This strain—isolated from a traditional cheese—produces putrescine, one of the most frequently biogenic amines found in dairy products.